Application of Chebyshev's inequality in stochastic differential equations - 494435 Zaitun Akmar Mahyuddin; Arifah Bahar; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2007